Exploring the relationship between dental pulp stones and ischemic cardiovascular diseases - Ezoddini Ardekani F.; Mohammadi Z.; Hashemian Z.; SadrBafghi M.; Hedayati A.; Rahmani Baghemalek MJ (Tehran University of Medical Sciences, 2009)
"nBackground and Aim: Dental pulp calcification may have the same pathogenesis as vascular calcifications. Pulp stones are calcified mass, which are commonly observed in usual dental radiographs. The purpose of this study was to evaluate the relationship between pulp stones and ischemic CVD. "nMaterials and Methods: This was a cross-sectional descriptive-analytic study on 20-25-year-old patients who had at least 8 intact teeth and were referred to Afshar hospital for cardiovascular examinations. Relationship between vascular stenosis and dental pulp stone was explored. "nResults: Sixty one patients who had undergone angiography were studied. They included 32 male (52.5%) and 29 female (47.5%). 38 patients had at least one stenotic vessel (from one to three vessels) and the others (37.7%) showed normal angiographic findings. 73.8% (31 cases) of the patients with dental pulp stones suffered from coronary narrowing where as only 36.8% (7 cases) of the patients without dental pulp stones showed coronary vessels narrowing. Pulp stones were mostly seen in first and second Molar teeth. "nConclusion: According to the results, we can state that oral and maxillofacial radiology is helpful in screening of cardiovascular diseases.